Un-settling the frontiers of food waste in the Netherlands: infrastructural stories of food waste transformation in the Hague - Vicherat Mattar, Daniela; Thrivikraman, Jyothi; Burgos Martínez, Elena (Frontiers in Sustainability, 2023)
Transformation opens possibilities to imagine and learn other forms of being and living together; it implies change, and often exchange. This paper visibilises the infrastructural stories involved in the transformation of food waste into edible food. Conceptually, we assume there is no univocal definition of food waste. Methodologically, we resist the practice of extracting and appropriating the life (hi)stories of the people involved in these transformative initiatives who are often described as vulnerable “others.” Instead, the project highlights the stories of the infrastructures underpinning these transformative experiences. The objective is to unsettle the frontier of what counts as food waste by paying attention to the objects involved in the process of transforming it into edible food. The paper starts by positioning ourselves in the literature regarding food waste governance and infrastructural labor as transformative possibilities that support the development of personal sustainability strategies and grassroots food governance. In the second section we explain our methodological considerations to focus on the infrastructures that mediate the transformation of disposed food into edible food in The Hague. The third section presents the results and discusses the stories of two objects, a cargo bike (bakfiets) and a fridge (koelkast). We suggest these objects serve to unsettle governance practices and narratives related to food waste in the city. Paying attention to these objects’ stories is an important turn in personal sustainability research because it enables us to see that the individual is never alone, always acting with the support of often invisible objects that in this study make possible the reduction and transformation of wasted food. This serves as inspiration to imagine alternative paths for food waste governance and foster forms of collective engagement, urgently needed given the increasing precariousness of food systems and relations.